Dampak Sosial Anak Pekerja Migran yang Tidak Dikehendaki Kelahirannya (Studi di Rumah Moch. Kholily Jember Jawa Timur) - Siti Noor Aini; Jeihan Ali Azhar (Institut Islam Nahdlatul Ulama Temanggung, 2019)
This study examines the social impacts of unwanted births by migrant workers at Moch. Kholily’s house in Jember, East Java. Plenty of unwanted birth rights violations cases by migrant workers raise a number of children’s basic rights issues, including the bad stigma of the children from the community, such as negative labels towards them as “anak oleh-oleh TKI”, “anak unta” and other abusive calls. The issue of negative social impacts even comes from their own extended family in the form of rejection of their presence to be a family member. Certainly, it violates the children’s rights, which is clearly opposing the Law of Indonesia Number 18 of 2017 on Protection of Indonesian Migrant Workers and their families. For this reason, this study is pivotal to be carried out through the sociological and phenomenological approach to explore any negative social impacts experienced by unwanted births children among the migrant workers at Moch. Kholily’s house Jember, East Java. The result of this study demonstrates that there are three categories of unwanted births. First is the unplanned births among migrant worker candidates prior to their placement in the destination country. Second is the unwanted births due to pregnancy through non-marital sexual intercourse among migrant workers. The third is the unwanted births due to sexual violence. While the social impacts on victims have been identified as follows: (1) issues of civil rights and freedom; (2) issues of familial rights and alternative care; (3) problems of child healthcare and basic welfare; (4) problems of education and family time for children.